The Effect of Using Verbal Mathematical Problem Solving on Developing Reading Comprehension among First Grade Middle School Students - Almaadi, Abdulaziz Saeed Yahya; Alqarni, Mousa Abdulmouin Mohammed (Journal of Curriculum and Teaching Methodology, 2023)
The current research aims to investigate the effect of using solving mathematical verbal problems in developing reading comprehension among first grade middle school student. The experimental approach (semi-experimental design) was used, by using a design with two control and experimental groups, through pre- and post-comparisons. The research sample was a group of first grade middle school student who were divided into two groups: a control group (25), and another experimental group (26), in the second semester of the academic year 1444 AH at the Al-Abnaa middle school affiliated with the Diriyah Education Office in the General Administration of Education in the Riyadh. The reading comprehension test was used after verifying its validity and reliability for the purpose of measuring the effect of using verbal mathematical problem solving in developing reading comprehension among first grade middle school student. The results indicated that there were statistically significant differences at the level of (0.05) between the average scores of the experimental group students in the pre- and post-applications on the total score of the reading comprehension test, and the differences were in favor of the post- test. The results also indicated that there were statistically significant differences at the level of (0.05) between the average scores of students in the experimental and control groups in the two post-applications on the total score of the reading comprehension test, the differences were in favor of the experimental group. Based on the research results, it is recommended to training first grade middle school student on reading comprehension skills in mathematics through various activities and training, and adding additional enrichment activities in Arabic language and mathematics courses.
Keywords: mathematics learning; mathematical verbal problems; reading comprehension; middle school